Nutrient composition of dried marine small fish in Bangladesh and their potential to address hidden hunger - Mamun, Abdullah-Al; Rifat, M. A.; Abdul, Wahab; Rahman, Muhammad; Nahiduzzaman, Md; Thilsted, Shakuntala; Kjellevold, Marian (Elsevier, 2024)
This study investigates the nutrient composition of fish powder intended for direct consumption, sourced from seven small fish species indigenous to the Bay of Bengal, Bangladesh. Locally known as chapila, chewa, faissa, ichre, loittya, mola, and olua, these fish were collected, dried to a moisture content consistent with local practices, pulverized, and subjected to analysis for proximate composition, mineral content, vitamin levels, heavy metal presence, and fatty acid profile. While the dried fish samples exhibited high nutritional quality, significant variations were observed among species for each nutrient analyzed. Consequently, no single species emerged as superior when considering all nutritional factors collectively. However, consuming 10 g of dried small fish powder sourced from the analyzed species could potentially fulfill 100% of the recommended nutrient intake (RNI) for protein, calcium, selenium, and vitamin B12 among children aged 6–23 months. Moreover, its serves as a significant source of these nutrients for pregnant or lactating women. Importantly, this intake level does not pose any risk associated with mercury or cadmium content. These findings hold promise as a valuable addition to the national food composition table, offering insights into the utilization of dried small fish from marine sources as a potent tool in the fight against malnutrition.